A study on contemporary identity of diaspora women writers (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The current study examines how modern Diaspora authors' works address mental and emotional health issues. In Diaspora literature, Identity Crisis is a result of numerous factors, including removal from one's home culture, the loss of one's original language, and the expatriate's status as a social outcast or unwelcome alien. Authors' exposure of their skill, which is based in the customs of society and culture, has been prompted by diaspora experiences including alienation, immigration, expatriation, exile, Identity Crisis, and Indianness. South Asian women's voices have been amplified by the avalanche of writing that has propelled the literary world of diasporas to new heights in the postmodern, globalized period. The literary achievements of these ladies have been widely celebrated and recognized in recent times. The inclusion of more people's perspectives also significantly increases its social significance. Such works clearly demonstrate a new coalition spanning international lines, challenging traditional literary conventions. Though the authors keep the diversity and uniqueness of countries around the world. It has also been noted that the majority of prominent Indian Diaspora authors are either first-generation or second-generation immigrants. They are the descendants of indentured workers and other third-wave migrants. Indians everywhere, at home and abroad, face the same challenges in life. The thesis only discusses female authors. The writing by women of the South Asian diaspora has been chosen because, as has been stated and examined in the preceding study, it demonstrates a feminist commitment and a collective aesthetic that distinguishes it from the literature of male South Asian Diasporic writers.